The ICPSR and Social Science Research - Johnson, Wendell G (Behavioral & social sciences librarian, 2008)
The Inter-university Consortium for Political and Social Research (ICPSR), a unit within the Institute for Social Research at the University of Michigan, is the world's largest social science data archive. The data sets in the ICPRS database give the social sciences librarian/subject specialist an opportunity of providing value-added bibliographic information. Access to the data sets is by membership in the consortium. This article gives an overview of the ICPSR database and of other services provided by the ICPSR, including sample usage statistics and reports. Research has shown that use of electronic resources, such as that provided by the data sets of the ICPSR, leads to an increase in publications by scholars. Librarians from a variety of disciplines--economics, political science, education, sociology, criminal justice, and social work--can help their researchers use the ICPSR's data sets to help further the goals of social science.